Body composition, body mass, and cardiovascular health in mid-childhood and midlife: a compositional data analysis - Liu, M; Dumuid, D; Olds, T; Burgner, D; Ellul, S; Juonala, M; Wang, Y; Ranganathan, S; Cheung, M; Baur, L; Dwyer, T; Kerr, JA; et al. (Mary Ann Liebert, 2025)
Background: We aimed to quantify associations of cardiovascular (CV) large and small artery measures with body composition and body mass (1) separately and (2) in combination in 11- to 12-year-old children and their parents. Methods: In the population-based cross-sectional Child Health CheckPoint study (1495 children, mean 12 ± 0.4 years, 49.3% girls; 1496 parents, mean 44.3 ± 5.0 years, 86.7% mothers), we measured weight, height, body composition [truncal fat, non-truncal fat, fat-free mass (FFM)], and CV functional (blood pressure, pulse wave velocity, arterial elasticity) and structural (carotid intima-media thickness, retinal arteriolar/venular caliber) outcomes. Using compositional data analyses, we examined associations of body composition (expressed as log ratios) and body mass (multiplicative total) with CV measures in separate and combined models. Results: Mean BMI z-score was 0.3 in children [standard deviation (SD) 1.0, 4.5% obese], and mean BMI was 27.9 in parents (SD 6.1, 28.8% obese). In both children and adults, more adverse CV measurements were associated with higher %truncal fat, %non-truncal fat, and body mass and lower %FFM. Compared with normal-weight children, children with obesity had poorer CV measures (e.g., 1 SD faster pulse wave velocity, 0.5 SD lower arterial elasticity), with higher body mass and lower %FFM mainly accounting for these relationships. All relationships were similar, albeit larger, for parents. Conclusion: Poorer CV health in both generations was associated with higher body mass, lower %FFM, and, to a lesser extent, higher %truncal and non-truncal fat. Trials could test whether weight reduction interventions with vs. without FFM preservation differentially improve CV functional and structural precursors.